2019
DOI: 10.1177/1526602819849955
|View full text |Cite
|
Sign up to set email alerts
|

Acute Outcomes With a Novel Plaque Modification System in Real-World Femoropopliteal Lesions

Abstract: Purpose: To report outcomes of a multicenter feasibility study using the FLEX Vessel Prep (VP) System, a novel technology that facilitates plaque incision and lumen gain in stenosed or occluded femoropopliteal arteries prior to balloon angioplasty. Materials and Methods: Two hundred fifty-five patients (mean age 71.8±9.1 years) were treated with the FLEX VP System at 38 centers between December 2015 and November 2017. Average lesion length was 133±88 mm. Average baseline stenosis was 92%±11%; 112 (44.3%) of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…To deal with the challenges related to calcification, either plaque modification by atherectomy, 20 vessel preparation devices, 21 or sufficient predilation could be keys for improving long-term patency of DCS. In the DEFINITIVE AR trial in which patients were randomized to directional atherectomy (DA) followed by DCB angioplasty or DCB angioplasty alone, 20 combined DA and DCB therapy tended to produce superior patency even though the number of patients was too small to show statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…To deal with the challenges related to calcification, either plaque modification by atherectomy, 20 vessel preparation devices, 21 or sufficient predilation could be keys for improving long-term patency of DCS. In the DEFINITIVE AR trial in which patients were randomized to directional atherectomy (DA) followed by DCB angioplasty or DCB angioplasty alone, 20 combined DA and DCB therapy tended to produce superior patency even though the number of patients was too small to show statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…The acute results of low dissection severity and provisional stent rate of 16.9% support a prospective study by Zeller and colleagues who reported provisional stenting in 19.2% of 255 patients with long femoral-popliteal lesions (133±88 mm) treated with FLEX VP prior to conventional endovascular treatment. 13 Furthermore, the stent rate and stent length are lower than the 32% to 35% bailout rate and 168.4 mm, respectively, reported in previous studies in DCB-treated patients with long lesions (>14 cm). 7,8 Focusing in on the longest lesions, provisional stents were required in 22.7% of lesions >25 cm (5/22) relative to a 50.9% reported in the this long-lesion cohort by Scheinert and colleagues.…”
Section: Discussionmentioning
confidence: 64%
“…11 This mechanism of action is intended to provide immediate improvement in vessel compliance and lumen gain with a predictable plaque modification to reduce the acute need for bailout stent placement and improve long-term outcomes, both potentially significant improvements in peripheral arterial disease (PAD) management. 12 The micro-incision approach may also facilitate dilatation of the stenosis at lower balloon inflation pressures, 13 reducing the barotrauma that may potentiate restenosis. This retrospective study was designed to assess the acute and long-term outcomes in patients who received vessel preparation via FLEX VP prior to PTA for SFA and PA.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of serious adverse events and the low complication rate related to the FLEX VP procedure (<3%) confirm the safety record previously reported for this endovascular device in subjects with peripheral artery disease. [15][16][17] No major complications were reported in either the fistula or graft cohort. This is in keeping with the JVIR Quality Improvement Guidelines thresholds of 2% (AVF) and 7% (AVG).…”
Section: Discussionmentioning
confidence: 99%
“…14 This mechanism of action creates microincisions that release the circumferential tension and is intended to provide immediate improvement in vessel compliance and lumen gain with the intention to reduce the acute need for high-pressure PTA and associated barotrauma that may be a stimulus for restenosis. 15,16 This study aimed to evaluate the outcomes associated with FLEX VP prior to PTA for AV access in a prospective, observational registry (FLEX-AV registry) with planned 12-month follow-up. This interim analysis introduces the procedural results of the endovascular interventions and 6-month outcomes in HD access when the FLEX VP system is utilized in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%